Inequalities for a Unified Integral Operator for Strongly α,m-Convex Function and Related Results in Fractional Calculus - Chahn Yong Jung; Ghulam Farid; Kahkashan Mahreen; Soo Hak Shim (Journal of Function Spaces)
In this paper, we study integral inequalities which will provide refinements of bounds of unified integral operators established for convex and α,m-convex functions. A new definition of function, namely, strongly α,m-convex function is applied in different forms and an extended Mittag-Leffler function is utilized to get the required results. Moreover, the obtained results in special cases give refinements of fractional integral inequalities published in this decade.